SEPARATION OF LIQUID BINARY MIXTURES BY RECTIFICATION WITH ADDITION OF SUBSIDIARY COMPONENT - V. M. Raeva; L. A. Serafimov; K. A. Morozov; T. V. Poroshina (Тонкие химические технологии)
The industrial separation of binary azeotropic mixtures and mixtures with relative volatilities of substances close to 1 uses special rectification techniques with an addition of a third component. These methods are classified by the main characteristics: by the volatility of the additive in the case of extractive and re-extractive rectification, and also by the change in the number of liquid phases of the system after the introduction of a new component in the case of heteroazeotropic rectification. The main problems in the field of extractive distillation, the most popular industrial method of separating azeotropic mixtures that require further theoretical study are formulated. The review includes primarily theoretical studies performed in different years at the department of chemistry and technology of basic organic synthesis of Lomonosov Moscow State University of Fine Chemical Technologies and is dedicated to special methods of distillation of binary azeotropic mixtures